2006
DOI: 10.1007/s10916-006-9022-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Satisfaction Level with the Food Services in a Military Hospital

Abstract: The variances in total test expenditures for different academic careers and specialties indicate the need to standardize the treatment process for asthma and to reconsider medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 21 publications
9
34
1
2
Order By: Relevance
“…These dimensions have been mentioned in other studies as being compromised and affecting patients' food consumption. 20,22,24 Hence, these dimensions should be improved to gain higher patient confidence in hospital foodservice in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These dimensions have been mentioned in other studies as being compromised and affecting patients' food consumption. 20,22,24 Hence, these dimensions should be improved to gain higher patient confidence in hospital foodservice in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is evident that education level determined the level of patient satisfaction, 41 some studies have reported contradicting findings as well. 14,24 Nonetheless, the influences of academic background on the level of satisfaction should be acknowledged, as those patients with a higher education level tend to be more knowledgeable, have higher expectations, and not easily satisfied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No obstante, el tipo de dieta o la presencia de sal en la misma no se asoció en nuestro estudio a un aumento significativo de la satisfacción con la dieta de los pacientes. En este sentido, otras investigaciones no observan relaciones estadísticamente significativas con la satisfacción alimentaria entre las diferentes dietas hospitalarias (17,31,32). Por otro lado, un 66,8% de los pacientes refirieron ingresos previos en el centro, cuestión que plantea a favor del estudio que poseen experiencia en cuanto a la alimentación percibida.…”
Section: Discussionunclassified